2019
DOI: 10.1152/advan.00197.2018
|View full text |Cite|
|
Sign up to set email alerts
|

Factors influencing the National License Examination step 1 score in preclinical medical students

Abstract: The National License Examination step 1 (NLE1), which tests basic medical sciences knowledge in Thailand, is considered to be tough and stressful for medical students due to the large amount of content. This study aimed to determine factors influencing the NLE1 score (NLE1S). The NLE1S, academic achievement, and class attendance were obtained officially. Other factors, including study habits, were obtained via a questionnaire, with 81.97% (241/294) being returned. Students were divided into four groups accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 34 publications
(43 reference statements)
5
12
0
4
Order By: Relevance
“…Y. Kim, Kim, Park, Kim, & Choi, 2017;Lertwilaiwittaya et al, 2019) had a positive effect on study outcomes, while time spent on non-academic internet use (AlFaris et al, 2018;Azizi, Soroush, & Khatony, 2019;Lertwilaiwittaya et al, 2019) and recorded-e-lecture study (Eisen et al, 2015; S. Y. Lertwilaiwittaya et al, 2019) had a negative effect. Class attendance has inconsistent results.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Y. Kim, Kim, Park, Kim, & Choi, 2017;Lertwilaiwittaya et al, 2019) had a positive effect on study outcomes, while time spent on non-academic internet use (AlFaris et al, 2018;Azizi, Soroush, & Khatony, 2019;Lertwilaiwittaya et al, 2019) and recorded-e-lecture study (Eisen et al, 2015; S. Y. Lertwilaiwittaya et al, 2019) had a negative effect. Class attendance has inconsistent results.…”
Section: Introductionmentioning
confidence: 96%
“…For the regulatory instruments, previous studies showed that highly expected examination score was positively associated with academic outcomes (Elliot, McGregor, & Gable, 1999;Lertwilaiwittaya et al, 2019;Sitticharoon et al, 2014). For the regulatory mechanisms, high motivation to study medicine (Frischenschlager, Haidinger, & Mitterauer, 2005;Kusurkar, Ten Cate, van Asperen, & Croiset, 2011;Pinyopornpanish et al, 2004;Stegers-Jager, Cohen-Schotanus, & Themmen, 2012), high percentage of study target achievement (Lertwilaiwittaya et al, 2019), regular lesson review (Lertwilaiwittaya et al, 2019;Lumley, Ward, Roberts, & Mann, 2015), and time spent on academic-internet use (Eisen et al, 2015;S. Y. Kim, Kim, Park, Kim, & Choi, 2017;Lertwilaiwittaya et al, 2019) had a positive effect on study outcomes, while time spent on non-academic internet use (AlFaris et al, 2018;Azizi, Soroush, & Khatony, 2019;Lertwilaiwittaya et al, 2019) and recorded-e-lecture study (Eisen et al, 2015; S. Y.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicate the select noncognitive factors of grit, locus of control, the Big Five Personality Traits, and perceived stress may be associated with learning and academic success among health professions students. [9][10][11][12][13][14][15][16][17][18][19][20] For example, studies conducted by Munro 19 , Ofori and Charlton 14 , and Webb et al 20 , found higher internal locus of control (or perceptions of control over one's life) was associated with better academic performance among nursing and medical students. Among 16 studies specifically in pharmacy A J P E A c c e p t e d D r a f t were calculated to determine internal consistency (reliability) of the instruments.…”
Section: Introductionmentioning
confidence: 99%